Water management strategies for run‐of‐river power plants: Profitability and hydrologic impact between the intake and the outflow. Issue 12 (11th December 2013) - Lazzaro, G.; Basso, S.; Schirmer, M.; Botter, G.
<x xml:space="preserve">Abstract</x> [1] In Alpine regions, especially when energy production by run‐of‐river plants is subsidized through state incentives, the indiscriminate growth of small plants built in cascade along the same river threatens aquatic ecosystems by depleting significant fractions of the river network. This paper compares the economic profitability of small run‐of‐river power plants and the ensuing hydrologic disturbance between the intake and the outflow, as resulting from the adoption of two alternative management strategies, namely the minimum flow discharge and a percent‐of‐flow rule. The capacity that maximizes the produced energy or the economic value of the plant, as well as the flow regime between the intake and the outflow, are analytically expressed as a function of the frequency distribution of the available streamflows. A quantitative framework relying on a set of synthetic hydrologic and economic indices is then proposed to compare the effectiveness of management strategies. The application of the method to three case studies in North‐Eastern Italy evidences that the compliance of the minimum flow discharge does not prevent huge alterations of some key attributes of the flow regime, especially the temporal flow correlation. For a given and equal economic profitability of the investment, the two management strategies produce similar ecodeficits and an analogous reduction of the mean discharge between the intake and the outflow. However, the percent‐of‐flow strategy allows a reduced disturbance on the temporal correlation and the skewness of river discharges. Furthermore, when a percent‐of‐flow strategy is implemented, possible policy redefinitions aimed at reducing the hydrologic disturbance of the plant in the reach between the intake and the outflow can be complied with at reduced costs in terms of missed energy production. The framework developed may be a valuable tool to assess the ability of water management strategies to trade between hydrologic disturbance and anthropogenic uses of fresh water.